Symposium 4: Should the Use of Different Research Models for Networked Learning Lead to Different Results? - Alsop, Graham; Tompsett, Chris (Proceedings of the International Conference on Networked Learning, 2004)
This paper investigates the relationship between two theoretical models of research (Grounded Theory and Activity Theory), research design and research outcomes. Taking a previous study of networked learning using Ground Theory as a reference point, these issues are considered in two stages, firstly we consider the differences that should result if the theoretical views are followed systematically and secondly, the particular tools and processes that should be used. The differences discussed suggest that the theoretical basis for a methodology should, and does, have an effect on the research outcomes. If we are to progress in networked learning researchers should, at the very least, understand how different models ought to be applied and apply them consistently.